Virtual Screening of Dihydropyrimidinone (DHPM) and Chromene Derivatives as Novel Inhibitors of SARS-CoV-2 Papain-like Protease - Adriaty, Dinar; Hery Suwito; Ardiana Ilham Nurrohman; Ni Nyoman Tri Puspaningsih (Indonesian Journal of Tropical and Infectious Disease, 2026)
SARS-CoV-2 Papain-like protease (PLPro) is an essential enzyme involved in viral replication and immune evasion, making it an attractive target for antiviral drug discovery. In addition to processing viral polyproteins, PLPro removes ubiquitin and ISG15 from host proteins, contributing to immune suppression. Therefore, the identification of compounds capable of interacting with PLPro may support the development of antiviral therapeutic strategies against coronavirus infections.  This study employed virtual screening of dihydropyrimidinone (DHPM) and chromene derivatives to prioritize compounds with favorable predicted interactions with SARS-CoV-2 PLPro.  Despite their broad biological activities, these scaffolds have not been extensively explored against viral proteases. A preliminary in vitro study showed that there were two lead compounds, DHPM (S-12) and chromene (S-10), which showed good inhibitory activity against SARS-CoV-2 with IC₅₀ values of 6.187 ± 0.41 μM and 8.52 ± 0.28 μM, respectively, thereby establishing them as promising antiviral lead compounds. Based on these findings, the current research aims to design new derivatives of DHPM and chromene compounds by introducing 14 functional groups to the aromatic rings of these lead compounds. As a result, a database of 420 new derivatives was generated. The screening process employed a selection score (SS) system based on ADMET properties and docking scores, allowing for the identification of the highest-ranked in comparison to reference drugs. Three compounds were identified: S12-92, S12-98, and S12-2-60, all of which were DHPM derivatives. These compounds are proposed as potential PLPro-binding candidates for further development as anti-SARS-CoV-2 drugs due to their favorable pharmacokinetic profiles and docking results.